2020
DOI: 10.1152/ajpregu.00358.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sympathectomy reduces peripheral inflammatory responses to acute and chronic sleep fragmentation

Abstract: Sleep loss contributes to the development of cardiovascular, metabolic, and neurological disorders by promoting a systemic proinflammatory phenotype. The neuroendocrine-immune mechanisms contributing to such pathologies are poorly understood. The sympathetic nervous system (SNS) regulates immunity and is often activated following sleep disturbances. The aims of this study were to determine 1) the effect of SNS inhibition on inflammatory responses to sleep fragmentation (SF) and 2) whether homeostasis can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 36 publications
10
41
0
Order By: Relevance
“…While effects of acute sleep loss on SNS and HPA activity can be considered mild or adaptive, chronic sleep loss caused by OSA, shift work, and modern lifestyles can contribute to more deleterious effects such as cardiovascular and metabolic disease, obesity and neurological disorders (Schwartz et al, 1999;Mavanji et al, 2012). Our laboratory previously showed that SF-induced increases in cytokine gene expression and serum proteins were mitigated by chemical sympathectomy, confirming that inhibition of the SNS reduces inflammatory responses from acute and chronic SF (Mishra et al, 2020). However, it is unknown how NE is acting on these target tissues to regulate inflammation.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…While effects of acute sleep loss on SNS and HPA activity can be considered mild or adaptive, chronic sleep loss caused by OSA, shift work, and modern lifestyles can contribute to more deleterious effects such as cardiovascular and metabolic disease, obesity and neurological disorders (Schwartz et al, 1999;Mavanji et al, 2012). Our laboratory previously showed that SF-induced increases in cytokine gene expression and serum proteins were mitigated by chemical sympathectomy, confirming that inhibition of the SNS reduces inflammatory responses from acute and chronic SF (Mishra et al, 2020). However, it is unknown how NE is acting on these target tissues to regulate inflammation.…”
Section: Introductionmentioning
confidence: 88%
“…The following protocols were described previously by Mishra et al (2020). Briefly, RNA was extracted from EOWAT, heart, liver, spleen, and brain tissue using RNeasy mini kits (Qiagen).…”
Section: Real Time-pcrmentioning
confidence: 99%
See 3 more Smart Citations